Decentralization Reform and Prospects for Economic Development in Ukraine: Impact Assessment - Vasyl MARCHUK; Nataliya MARCHUK; Olha YEMETS (Communications of International Proceedings, 2020)
A thorough and systematic reform of local self-government has been launched since 2014 in Ukraine. The experience of Central and Eastern European countries in combination with international standards and recommendations for the positioning of the institution of municipalities is entrusted to the development of relevant legislation and mechanisms for the practical implementation of change. The updated legal framework has significantly contributed to the municipal consolidation in the country and created the appropriate legal conditions for the implementation of the developed reform and the effective functioning of local authorities and economies. The study analyzes and evaluates a new phenomenon for Ukraine - political and economic decentralization of power and it’s impact on economic development. The reform is carried out in favor of the formation of the basic level of government through the formation of new primary structures - united territorial communities. The influence of the principle of subsidiarity on the formation of local self-government structures on the economic development of communities is studied. The first stage of decentralization reform is generalized taking into account the projected changes, real results and expected risks.
Keywords: decentralization; united territorial community; economic development; investment.